2009
DOI: 10.1242/jcs.045021
|View full text |Cite
|
Sign up to set email alerts
|

Homophilic and heterophilic polycystin 1 interactions regulate E-cadherin recruitment and junction assembly in MDCK cells

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited human renal disease and is caused by mutations in two genes, PKD1 (85%) and PKD2 (15%). Cyst epithelial cells are characterised by a complex cellular phenotype including changes in proliferation, apoptosis, basement membrane composition and apicobasal polarity. Since polycystin 1 (PC1), the PKD1 protein, has been located in the basolateral membrane of kidney epithelial cells, we hypothesised that it might have a key role in media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
0
39
0
2
Order By: Relevance
“…Several abnormalities in the polarized distribution of membrane proteins and cell-cell contact proteins such as E-cadherin have been reported in ADPKD in cyst-lining epithelia (29). Recently, the polycystin complex has been implicated in junction formation and establishment of apicobasal polarity (31). In addition, it has been shown that PATJ, among other polarity proteins such as PALS1 and PAR6, interacts with nephrocystins, suggesting a link between tight junction formation and cystic kidney disease (32).…”
Section: Resultsmentioning
confidence: 99%
“…Several abnormalities in the polarized distribution of membrane proteins and cell-cell contact proteins such as E-cadherin have been reported in ADPKD in cyst-lining epithelia (29). Recently, the polycystin complex has been implicated in junction formation and establishment of apicobasal polarity (31). In addition, it has been shown that PATJ, among other polarity proteins such as PALS1 and PAR6, interacts with nephrocystins, suggesting a link between tight junction formation and cystic kidney disease (32).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous examples of G proteins regulating transmembrane proteins, especially ion channels (reviewed in Ref. 35), and PC1 was recently shown to function as an adhesion molecule (15). We recently identified G␣ 12 regulation of integrins through an inside-out signaling mechanism (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are other potential overlapping pathways between G␣ 12 and PC1. For example, PC1 regulates junction assembly in MDCK cells (15), and G␣ 12 interacts with ZO-1 in the tight junction and with E-cadherin to regulate tight junctions and cell adhesion (16,17). Finally, the G␣ 12 family regulates stress fiber formation and numerous other fundamental cellular processes, including proliferation, transformation, and cell migration (reviewed in Ref.…”
mentioning
confidence: 99%
“…E-cadherin is one of the most important components in the PC1 complex. The association of E-cadherin molecules is very important for maintaining the integrity of E-cadherin-mediated adherens junctions in MDCK cells (Streets et al, 2009). N-cadherin and E-cadherin can also form heterodimers in adherens junctions through heterophilic binding (Prakasam et al, 2006), which suggests that their association might be very important for cystic epithelial cell-cell contacts, and also for contacts between cystic and surrounding normal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%